2016
DOI: 10.1017/s0022215116007970
|View full text |Cite
|
Sign up to set email alerts
|

Does topical use of autologous serum help to reduce post-tonsillectomy morbidity? A prospective, controlled preliminary study

Abstract: In tonsillectomy patients, topically administered autologous serum contributed to throat pain relief and tonsillar fossa epithelisation during the post-operative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Throat ache is a complaint that frequently develops following tonsillectomy surgery and it may lead to undesired situations such as prolonged hospitalization, poor oral intake, dehydration, and late return to daily life. In the past, several agents were used to relieve pain following tonsillectomy [ 1 - 6 ] and they each have individual advantages and disadvantages. For that reason, there is currently not a consensus on relieving pain after tonsillectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Throat ache is a complaint that frequently develops following tonsillectomy surgery and it may lead to undesired situations such as prolonged hospitalization, poor oral intake, dehydration, and late return to daily life. In the past, several agents were used to relieve pain following tonsillectomy [ 1 - 6 ] and they each have individual advantages and disadvantages. For that reason, there is currently not a consensus on relieving pain after tonsillectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The pain persists until approximately 2–3 weeks as the pharyngeal muscles are covered by the mucosa. In order to relieve postoperative pain following tonsillectomy, several methods and medical therapeutic agents have been used such as hyaluronic acid [ 1 ], magnesium [ 2 ], opioid [ 3 ], honey intake [ 4 ], sucralfate in the tonsil region [ 5 ], and autologous serum [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…epithelisation and even cognitive dysfunction, may occur in patients after tonsillectomy (37). A previous study has reported that cognitive dysfunction may affect children for up to 6 months after the operation (13).…”
Section: Dex (Mg/kg) Adverse ----------------------------------------mentioning
confidence: 98%
“…Y Surgicel® [77]N for othersBismuth subgallate-basedBSG- adrenaline paste, BSG- phenylephrine hydrochloride mixtureY [78]Y (BSG mixed with phenylephrine hydrochloride) [79]Y BSG with adrenaline for primary PTH [80], N for secondary PTH [81]N [81]Clinical study on patients underwent tonsillectomy [78, 81]Spectrum Chemical (powder), mixing 26 g of BSG powder to 20 ml of normal saline with 0.7 ml of 1:1000 adrenalinePost-opdecreases operating time by significantly reducing the hemostasis time and the number of ligatures [78, 81]; accelerates the cascade of blood clotting [79]; accelerate the intrinsic clotting pathway through the activation of factor XII (Hageman factor) [82]. Y [62]Antifibrinolyticstranexamic acid (TXA) liquidY [83, 84]N [83, 84]Clinical reports analysis of 246 patients topically treated with TA and 248 control [84]Systematic review [83]Cyklokapron®Postopno device or site for infection, reduce intraoperative blood loss during Orthognathic Surgery, prevent postop hemorrhage after oral or dental surgery in hemophilia A patients and those on warfarin anticoagulation [85]N for Topical applicationNatural materialPropolisY [86]Y [86]Randomized controlled study on 65 patients [86]Topical propolis gelgargle immediately after surgery [86]accelerated wound healing of tonsillar fossaeNHerbal ingredientsY [87]Clinical trial in 47 consecutive children patientsAnkaferd Blood Stopper®Intra-opsafe and efficient, and it reduces operating time [87], and contains no synthetic additives [88]NAutologous serumY [89]Y [89]A preliminary study on 32 patients (4–15 years old) [89]Centrifuge peripheral venous blood at 1500–2000 g for 10 min to separate the serum and then topically administeredIntra and post 8 and 24 hContributed to tonsillar fossa epithelizatio...…”
Section: Main Text: Topical Biomaterials Used For Pthmentioning
confidence: 99%